Rotational IMRT techniques compared to fixed gantry IMRT and tomotherapy: multi-institutional planning study for head-and-neck cases - Wiezorek, Tilo; Brachwitz, Tim; Georg, Dietmar; Blank, Eyck; Fotina, Irina; Habl, Gregor; Kretschmer, Matthias; Lutters, Gerd; Salz, Henning; Schubert, Kai; Wagner, Daniela; Wendt, Thomas G. (Radiation oncology, 2011)
Recent developments enable to deliver rotational IMRT with standard C-arm gantry based linear accelerators. This upcoming treatment technique was benchmarked in a multi-center treatment planning study against static gantry IMRT and rotational IMRT based on a ring gantry for a complex parotid gland sparing head-and-neck technique.